2018
DOI: 10.1080/00343404.2018.1510178
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of collaborative partnerships between knowledge-intensive business service (KIBS) and product companies: the case of Bremen, Germany

Abstract: Regional science research is silent on how collaborative partnerships between KIBS and product companies emerge. Our paper addresses this theoretical gap by examining the role played by KIBS firms and by their interactions with product companies. We propose a typology of territorial servitization-namely knowledge gap, regulation gap, and capacity gap-wherein KIBS firms respectively play the pivotal roles of knowledge brokers, intermediators, and integrators in driving collaborative partnerships. By conducting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 34 publications
2
40
0
1
Order By: Relevance
“…One of the premises of territorial servitization is that geographical proximity is important in developing strong partnerships between manufacturing and service industries; however, with the exceptions of Liu et al (2019) this premise has not been evaluated empirically (Lafuente et al, 2019). In this special issue, two articles analyze this issue in-depth.…”
Section: Geographical Proximity Between Kibs and Manufacturing Firmsmentioning
confidence: 99%
“…One of the premises of territorial servitization is that geographical proximity is important in developing strong partnerships between manufacturing and service industries; however, with the exceptions of Liu et al (2019) this premise has not been evaluated empirically (Lafuente et al, 2019). In this special issue, two articles analyze this issue in-depth.…”
Section: Geographical Proximity Between Kibs and Manufacturing Firmsmentioning
confidence: 99%
“…However, the existing literature reviewed revealed some caveats that raise doubts about the general applicability of the results of these innovation collaborations between the science system actors and firms in the enterprise group. For instance, most of these empirical studies focused on countries classified as innovation leaders and those with strong innovation potential, such as the United Kingdom, Denmark, France, Germany, and Sweden among others (Banal-Estañol et al 2015;Kergroach et al 2018;Liu et al 2019). These studies demonstrated that these R&D collaborations are noticeable in these innovation leaders and strong innovative countries, but they differ significantly and are almost completely rare in new EU countries, such as Hungary and the Czech Republic, classified as moderate innovators still undergoing structural changes from communism to market economies.…”
Section: Introductionmentioning
confidence: 99%
“…Third, by examining the role played by foreign hospitals in fostering health system reforms, we extend the previous work on public-private collaborative partnerships (Xing et al, 2018). However, collaborative partnerships need to seek, establish, and sustain relationships with partners appropriate for the achievement of favorable performance outcomes (Collinson & Liu, 2017;Liu, Lattemann, Xing, & Dorawa, 2018). A microfoundational perspective is critical to advance international management research (Verbeke & Calma, 2017).…”
Section: Limitations and Future Research Directionsmentioning
confidence: 89%